2023
DOI: 10.1136/bmjpo-2022-001687
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for imaging abnormalities after the first febrile urinary tract infection in infants ≤3 months old: a retrospective cohort study

Abstract: ObjectivesTo assess the association of clinical factors and investigation results (blood and urine) with imaging abnormalities (ultrasound of the kidneys, ureters and bladder; dimercaptosuccinic acid scan; and/or micturating cystourethrogram) and recurrent urinary tract infections (UTIs) in infants ≤3 months old presenting with their first febrile UTI.MethodsWe conducted a retrospective cohort study of infants ≤3 months old with first febrile UTI admitted from 2010 to 2016. Multivariable logistic regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In our study, the incidence of UTIs was the highest in the 61-90 days age group. A previous single-center retrospective study investigating UTIs in infants ≤3 months old demonstrated a median age of 63 days [16] and consistent trends in epidemiology.…”
Section: Discussionsupporting
confidence: 59%
“…In our study, the incidence of UTIs was the highest in the 61-90 days age group. A previous single-center retrospective study investigating UTIs in infants ≤3 months old demonstrated a median age of 63 days [16] and consistent trends in epidemiology.…”
Section: Discussionsupporting
confidence: 59%
“…Another parameter strongly related to malformations is infection with a non‐ E. coli pathogen 10,11,21 . In our study, having an infection with an atypical pathogen increased the probability of underlying malformations by four times.…”
Section: Discussionmentioning
confidence: 48%
“…19 Different studies have identified various risk factors associated with NUM, and some heterogeneous recommendations have been made based on these criteria. 10,11,20,21 However, until now, there has yet to be a predictive model with good predictive capacity, based solely on clinical and analytical parameters, capable of stratifying patients into risk groups for individualised imaging protocols.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations